The standard bearer of the Roman church Lawrence of Brindisi & Capuchin missions in the Holy Roman Empire (1599-1613) - Drenas, Andrew J. G. 1983- (Washington, D.C. The Catholic University of America Press, 2018)
"This book examines the missionary work of the Capuchin friar and doctor of the Church Lawrence of Brindisi, who led the first organized Capuchin mission among the non-Catholics of Bohemia and worked extensively for the pope in Central Europe"--
Lawrence of Brindisi's career and afterlife -- The foundation of the commissariate of Bohemia-Austria-Styria -- Polemical preaching -- Theological disputations -- The express image of Lutheranism
Literaturverzeichnis Seite 223-238
Mit Register
Keywords: Lawrence -- of Brindisi, Saint -- 1559-1619; Capuchins -- Missions -- Holy Roman Empire -- History -- 17th century; Catholic Church -- History -- 17th century; Counter-Reformation -- Holy Roman Empire